Effect of enriched compost and crop establishment methods on productivity and profitability of rice (Oryza sativa) - GOUDA, HIMANSU SEKHAR; SINGH, Y V; SHIVAY, Y S; BISWAS, D R; S, POORNIMA; M, MANU S (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during kharif 2018-19 at ICAR-IARI, New Delhi to study the effect of rice (Oryza sativa L.) establishment methods and enriched organic nutrient sources on growth and productivity of rice. The experiment was laid out in split plot design with three replications having two main plot treatments, viz. aerobic rice (AR) and conventional transplanted (CT) rice and five sub plot treatments, viz. Control (No fertilizer), 100% RDF (100% mineral fertilization), 50% P through P enriched compost + 50% P through DAP, 50% N through N enriched compost + 50% N through urea and DAP and 100% organic (through N enriched compost and P enriched compost). Results showed that plant growth, productivity and profitability were significantly superior in CT rice than AR. Among the nutrient management options, 50% N through N enriched compost + 50% N through urea and DAP resulted in significantly higher grain yield (4.85 and 5.13 t/ha), gross (₹ 1.35 lakh and 1.43 lakh) and net return (₹ 85 lakh and 0.85 lakh) and yield attributes than other treatments and it was at par with 50% P through P enriched compost + 50% P through DAP in both the years. Hence, the conventional transplanting of rice along with integrated application of enriched compost and inorganic fertilizer may be recommended to farmers for getting higher productivity and profitability in rice.